Governing the Process, Quality and Administration of Outsourced IT Project - Chia, Su Guan (2006)
The need for faster, cheaper and more reliable software applications with fewer resources had created a greater demand for organizations to turn to outsourcing software development. Outsourcing provided a quick solution to this demand; however it is also clearly evidenced that poorly managed outsourcing resulted increased cost, delayed in schedules and dubious quality work.